Schopenhauer e os conhecimentos intuitivo e abstrato - Souza, Eduardo Ramos Coimbra de [UNESP] (2014)
This study has as focus the theory of knowledge developed by Arthur Schopenhauer in the Book I of The world as will and representation. To perform it, we’ll merely focus on the side of the world as representation, the phenomenal reality, to look for unravel how to the german thinker explains the possibility of the knowledge. More specifically, the two ways of knowledge, the intuitive and the abstract, together with their own objects, the intuitive representation and the abstract representation, beyond the faculty of the knowledge responsible for each of one these objects. The investigation will try to bound the principles that render the world of representation, understandable, forming, in the end, a systematic theory of knowledge.